Foreign Aid and its Impacts on Cultural Norms of Islamic Society.An Analytical Study in the Light of Seerat-un-Nabi(SAW) - Dr. Sadia Gulzar (Seerat Studies, 2023)
Foreign Aid is provided for the assistance of a nation. Foreign economic assistance includes humanitarian, political and developmental aid. It may be granted to strengthen a military ally or for some special purposes. After the incident of 9/11, Pakistan became the ally of the United States and appeared as the biggest beneficiary of United States' military and economic assistance in South Asian region. United States has also granted aid to different Muslim countries for peace and for diplomatic and political stability. Nevertheless, every economic agenda of non-Muslim countries has a particular purpose. They are making Muslim countries financially weaker through conditional debts with high rate of interest. Contrary to this, teachings of Holy Prophet (SAW) have no space for any such economic policy which may exploit any individual or a group. Conditional aid of non-Muslim countries and donor organizations is distorting cultural and social norms in Islamic society. Islam strictly prohibits interest-based debt and conditional economic assistance. The Holy Prophet (SAW) accepted gifts from non-Muslims. However, He (SAW) did not accept any conditional debt or aid which could affect Islamic norms. Purpose of this research paper is to highlight the objectives of non- Muslim countries which are providing aid to Muslim countries and to analyze its impact on the Islamic norms in the light of Fiq Al-Seera. Research paper follows descriptive and analytical methods.